Art and magic in the court of the Stuarts - Hart, Vaughan, 1960- (Routledge, 1994)
Examines the influence of magic on Renaissance art in the context of the first Stuart Court. Here artists sought to represent magic as an expression of the Stuart King's Divine Right, and later of their policy of Absolutism.